Quantum Information and Measurement VI 2021 2021
DOI: 10.1364/qim.2021.m2a.5
|View full text |Cite
|
Sign up to set email alerts
|

Two-Rebit Entanglement: Theory and Experiment

Abstract: We characterize entanglement over real and complex, composite quantum systems. Methods are formulated and applied to simultaneously certify inseparability and separability for two rebits and two qubits, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The entanglement properties of rebits have also been investigated [48,70,71]. Recently, the entanglement of two rebits has been investigated in laboratories [72,73]. Redits are qudits with real coefficients.…”
Section: Average Quantum Coherence Of Typical Pure Statesmentioning
confidence: 99%
“…The entanglement properties of rebits have also been investigated [48,70,71]. Recently, the entanglement of two rebits has been investigated in laboratories [72,73]. Redits are qudits with real coefficients.…”
Section: Average Quantum Coherence Of Typical Pure Statesmentioning
confidence: 99%
“…Today, quantum mechanics with imaginary numbers seems to be the most successful theory to describe the microscopic world. These research contributions have shown that complex quantum mechanics is fundamentally different from the corresponding real version in many aspects [2,10,13,15,19,[24][25][26][27][28], revealing that the imaginary part is not only necessary for the formulation of quantum theory but also plays an important role in many quantum information tasks [9,11,29].…”
Section: Introductionmentioning
confidence: 99%
“…Today, quantum mechanics with imaginary numbers seems to be the most successful theory to describe the microscopic world. These research contributions have shown that complex quantum mechanics is fundamentally different from the corresponding real version in many aspects 2,10,13,15,19,[26][27][28][29][30][31] , revealing that the imaginary part is not only necessary for the formulation of quantum theory but also plays an important role in many quantum information tasks 9,11,32 .…”
mentioning
confidence: 99%